Report of case: Fluoxetine-associated symptomatic hyponatremia in the young woman without comorbidity - Gundogmus, Ibrahim; Beril Tasci, Azize; Akgun, Abdullah; Kaymak Polat, Derya; Bolu, Abdullah; Uzun, Ozcan (Annals of Medical Research, 2021)
None